STUDI PROTEKSI ELECTRIC SHOCK PADA INSTALASI RUMAH TINGGAL MENGGUNAKAN RESIDUAL CURRENT CIRCUIT BREAKER WITH INTERGRAL OVERLOAD PROTECTION - Sofyar Sofyar (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2021)
This paper offers a solution for securing a simple residential installation of the dangers of electric shock. In the introduction, the background of the importance of using a protection system in electrical installations is explained and some definitions related to electric shock and RCBO. For the part of the research method, the specifications of the RCBO used are displayed and the flow of the research is also shown. In the discussion and the results it is known that RCBO will trif if there is an overload, short circuit, and electric shock caused by direct contact with the live part. For nominal current (In) from RCBO, RCBO with a value of 6 Ampere and its current sensitivity (I∆n = 30 mA) is chosen according to the RCBO on the market.